1993
DOI: 10.1111/j.1469-8137.1993.tb03765.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium amelioration of aluminium toxicity effects on root hair development in soybean [Glycine max (L.) Merr.]

Abstract: SUMMARYLow activities of the monomeric aluminium (Al) species, AP+, AKOH)^" and A1(OH)2+ in solution reduce root growth and root hair development in soybean [Glycine max (L.) Merr.]. Calcium (Ca) ameliorates to a certain extent the toxic effects of Al on root growth, but the interactive effects of Ca and Al on root hair development are not known. In the absence of added Al in solution culture, Ca concentration over the range 500-2000 //M had little effect on root growth or root hair development of soybean cv. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 31 publications
2
51
1
1
Order By: Relevance
“…However, care must be taken when interpreting the results of Lane and Martin (1980), because the high P concentration used (2 mM) has been shown to -Page 14 -influence root hair growth (Foehse and Jungk 1983). The apparent lack of detrimental Pb 2+ effects on root hair growth is also in contrast to those observed for Al toxicity (Brady et al 1993;HechtBuchholz et al 1990) and Cu toxicity (Kopittke et al 2007b;Kopittke and Menzies 2006) in which root hair formation is reduced at lower metal concentrations than those required to reduce root elongation. In the present study, root hairs developed within 1 mm of the root tip (Figure 2i,k) indicating that cells close to the root tip were not killed by Pb 2+ but that there was a severe disruption of normal root development in which root hairs develop distal to the elongation zone.…”
Section: Influence Of {Pb 2+ } On Plant Growthcontrasting
confidence: 41%
“…However, care must be taken when interpreting the results of Lane and Martin (1980), because the high P concentration used (2 mM) has been shown to -Page 14 -influence root hair growth (Foehse and Jungk 1983). The apparent lack of detrimental Pb 2+ effects on root hair growth is also in contrast to those observed for Al toxicity (Brady et al 1993;HechtBuchholz et al 1990) and Cu toxicity (Kopittke et al 2007b;Kopittke and Menzies 2006) in which root hair formation is reduced at lower metal concentrations than those required to reduce root elongation. In the present study, root hairs developed within 1 mm of the root tip (Figure 2i,k) indicating that cells close to the root tip were not killed by Pb 2+ but that there was a severe disruption of normal root development in which root hairs develop distal to the elongation zone.…”
Section: Influence Of {Pb 2+ } On Plant Growthcontrasting
confidence: 41%
“…In lily pollen tubes grown in vitro, tip Ca 2+ and elongation rate oscillate regularly with large amplitudes (Messerli et al 2000). Growing root hairs have a high calcium gradient at the tip (Schiefelbein et al 1992) and calcium is essential for root hair growth in soybean (Brady et al 1993). This suggests that calcium-regulated pulsatile growth may be a general feature of extension growth of root hairs.…”
Section: Discussionmentioning
confidence: 99%
“…There are no obvious reasons why white clover root hair growth should be so slow, although root type of the experimental material used may be a contributing factor. The experiments reported here were all done on nodal roots but most root hair extension rates reported in the literature were obtained on seminal roots of seedling plants (Foehse & Jungk 1983;Brady et al 1993;Bates & Lynch 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased calcium can reduce the detrimental effects of aluminum on soybean (Lund 1970;Brady et al 1993) and nickel toxicity in corn (Robertson 1985). Calcium-nickel interactions can be complex, and Knight and Crooke (1956) found that the calcium uptake of oat plants, but not of tomato plants, was higher in nickel-contaminated soils .…”
Section: Introductionmentioning
confidence: 99%